Risk sensitive reproductive strategies : the effect of environmental unpredictability - Bårdsen, Bård-Jørgen (Universitetet i Tromsø, 2009)
Papers number 1 and 2 of the thesis are not available in Munin, due to publishers' restrictions: 1. Bårdsen, B.-J., P. Fauchald, T. Tveraa, K. Langeland, N. G. Yoccoz, and R. A. Ims: "Experimental evidence for a risk sensitive reproductive allocation in a long-lived mammal", Ecology (2008)89:829-837 (Ecological Society of America). Available at http://dx.doi.org/10.1890/07-0414.1 2. Bårdsen, B.-J., P. Fauchald, T. Tveraa, K. Langeland, and M. Nieminen: "Experimental evidence of cost of lactation in a low risk environment for a long-lived mammal", Oikos (2009)118:837-852. Available at http://dx.doi.org/10.1111/j.1600-0706.2008.17414.x A crucial task in ecology is to quantify trade offs between competing demographic processes for experienced by individuals that inhabit unpredictable environments. Perhaps the most widely studied trade off is that between current reproduction and future survival (‘the cost of reproduction’). While experimental studies have been widely used to quantify life history strategies in birds, virtually no experimental studies have been carried out on large and free ranging mammals. This thesis quantifies how female reindeer Rangifer tarandus subject to variability in food availability, trade their resources between reproduction and body mass to ensure own survival. By combining two experiments, one observational study and one theoretical model, this thesis show that: (1) Individuals subject to reduced food availability in one winter feeding promptly reduced their reproductive allocation the following summer to increased their autumn body mass. On the other hand, short-term improved conditions did not result in increased reproductive allocation. (2) Long-term improved winter feeding conditions did, however, result in increased reproductive allocation. (3) Reproduction was costly, especially for smaller females, as occasional harsh winters and high population density resulted in reduced reproduction and lowered female body mass. Moreover, a successfully reproducing female produced a smaller ...